? ACIDITY CONSTANT OF BENZALDEHYDE -2- HYDROXY AZINE ANO ITS CHELATION WITH Cu (II), Co (II) AND Ni (II) (Biological Sciences - PJSIR, 1996)
The acid dissociation constant of benzaldehyde-Z-hydroxyazine (H2A) is determined spectrophotometrically in aseries of universal buffer solutions (20% ethanol, v/v) of varying pH. Cu (II), Co (II) and Ni (II) omplexes of H2A havebeen prepared and characterized by elemental analysis, molar conductance, electronic and infrared spectra measurements.It is concluded that the ligand acts as bivalent ONNO tetradentate, The complexes are suggested to exhibit adistorted octahedral geometry.